👤
Didi151111
a fost răspuns

descompunerii în factori

Descompunerii În Factori class=

Răspuns :

Abc112
[tex]24) {x}^{2} + x - 6 [/tex]

[tex] = {x}^{2} + 3x - 2x - 6[/tex]

[tex] = x(x + 3) - 2(x + 3)[/tex]

[tex] = (x + 3)(x - 2)[/tex]

[tex]25) {x}^{2} + 4x - 12[/tex]

[tex] = {x}^{2} + 6x - 2x - 12[/tex]

[tex] = x(x + 6) - 2(x + 6)[/tex]

[tex] = (x + 6)(x - 2)[/tex]

[tex]26) {x}^{2} - 6x - 7[/tex]

[tex] = {x}^{2} - 7x + x - 7[/tex]

[tex] = x(x - 7) + x - 7[/tex]

[tex] = (x - 7)(x + 1)[/tex]

[tex]27) {x}^{2} - 11x - 12[/tex]

[tex] = {x}^{2} - 12x + x - 12[/tex]

[tex] = x(x - 12) + x - 12[/tex]

[tex] = (x - 12)(x + 1)[/tex]
ax^2 +bx +c =0
S=x1+x2 = - b/a
P=x1*x2 = c/a, cf formulelor lui Vièt.
ax^2 + bx + c = a(x-x1)(x-x2)
------------------------------------------
24) S= -1, P= -6 , x1= -3, x2=2
x^2 + x - 6 = (x+3)(x-2)

25) S= -4, P = -12 ⇒ x1= -6, x2= 2
= (x+6)(x-2)

26. S=6, P= -7 ⇒ x1=7, x2= -1
= (x-7)(x+1)

27. S=11, P= -12 ⇒ x1= 12, x2= -1
= (x-12)(x+1).